A Noninvasive Gut‐to‐Brain Oral Drug Delivery System for Treating Brain Tumors. Issue 34 (16th July 2021) - Miao, Yang‐Bao; Chen, Kuan‐Hung; Chen, Chiung‐Tong; Mi, Fwu‐Long; Lin, Yu‐Jung; Chang, Yen; Chiang, Chi‐Shiun; Wang, Jui‐To; Lin, Kun‐Ju; Sung, Hsing‐Wen
Abstract: Most orally administered drugs fail to reach the intracerebral regions because of the intestinal epithelial barrier (IEB) and the blood–brain barrier (BBB), which are located between the gut and the brain. Herein, an oral prodrug delivery system that can overcome both the IEB and the BBB noninvasively is developed for treating gliomas. The prodrug is prepared by conjugating an anticancer drug on β‐glucans using a disulfide‐containing linker. Following oral administration in glioma‐bearing mice, the as‐prepared prodrug can specifically target intestinal M cells, transpass the IEB, and be phagocytosed/hitchhiked by local macrophages (Mϕ). The Mϕ‐hitchhiked prodrug is transported to the circulatory system via the lymphatic system, crossing the BBB. The tumor‐overexpressed glutathione then cleaves the disulfide bond within the prodrug, releasing the active drug, improving its therapeutic efficacy. These findings reveal that the developed prodrug may serve as a gut‐to‐brain oral drug delivery platform for the well‐targeted treatment of gliomas. Abstract : Following oral administration, a prodrug transpasses the intestinal epithelial barrier via M cells, and then undergoes endocytosis by resident macrophages. The macrophage‐hitchhiked prodrug is transported to the circulatory system via the lymphatic system, crossing the blood–brain barrier, ultimately penetrating a brain tumor. The tumor‐overexpressed glutathione cleaves the disulfide bond within the prodrug, releasing the active drug, facilitating antitumor efficacy.